Three-dimensional flower-shaped pseudo-boehmite material with high specific surface area as well as preparation method and application of pseudo-boehmite material
The three-dimensional flower-shaped phthalic acid lithosaite material was prepared through rotary liquid film reactor and microwave hydrothermal crystallization technology, which solved the problem of poor adsorption effect of existing phthalic acid lithosaite and achieved efficient adsorption of phosphorus, fluorine and Congo red. Suitable for industrial applications.
Patent Information
- Application Number
- CN202411336653.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing pseudo-thin aluminite materials have poor adsorption effect on pollutants in water bodies and low active site density, resulting in slow adsorption rate and low maximum adsorption amount, limiting their industrial application.
Three-dimensional flower-shaped high specific surface area phthalite material is prepared by rotary liquid film reactor and microwave hydrothermal crystallization technology. The crystal surface nucleation and nanosheet assembly are regulated by surfactant to form a high specific surface area and (020) Nanostructures exposed on the crystal surface.
It significantly improves the adsorption performance of phosphorus, fluorine and Congo red, increases the adsorption capacity, simplifies the preparation process, reduces costs, and is suitable for large-scale production.
Smart Images

Figure CN119219037A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a three-dimensional flower-shaped pseudo-boehmite material with a high specific surface area, and a preparation method and application thereof. Background Art
[0002] With the development of industry, water pollution is becoming more and more serious. Water pollution refers to the reduction or loss of water use value caused by domestic sewage generated by people's lives, production wastewater discharged from agricultural and industrial activities and other pollutants.
[0003] Water eutrophication usually refers to the phenomenon of water pollution caused by excessive content of nutrients such as P and N in water. In addition, fluorine is also a common pollutant in water. It is one of the three types of carcinogens announced by the World Health Organization. Excessive intake can lead to a series of diseases such as fluorosis, causing serious harm to human health. The discharge of dye wastewater is also increasing. These dye wastewaters contain wastewater from industries such as textiles, papermaking, leather and plastics. Congo red (CR) is a water-soluble, benzidine-based anionic disazo dye that is toxic to many organisms because it is irritating to aquatic organisms and human skin and eyes. Therefore, exploring a simple, efficient and low-cost method to control pollutants in water bodies has become the primary goal in the field of water resource protection.
[0004] At present, the main methods for treating water pollution wastewater are degradation, catalysis and adsorption. Among them, the adsorption method is widely used because of its low cost and simple operation. In the current study, pseudo-boehmite has a high zero-point charge and a high specific surface area, which can provide abundant active sites. There are high-density hydroxyl groups on its (020) crystal surface, which has excellent adsorption and removal performance. However, when the existing pseudo-boehmite is used for the adsorption of pollutants in water bodies, the adsorption effect is poor, because its active site density is low, resulting in a slow adsorption rate and a small maximum adsorption amount, which limits its practical application. Shunzheng Zhao, Yanfeng Wen and Chengcheng Du, et al. Introduction of vacancy capture mechanism to defective alumina microspheres for enhanced adsorption of organic dyes, Chemical Engineering Journal, 2022, 402, 126180. It is reported that the currently prepared pseudo-boehmite has a low specific surface area, insufficient distribution of active sites, and a low adsorption capacity for pollutants. Lei Huang, Zhihui Yang and Yujun Shen, et al. Organic frameworks induce synthesis and growth mechanism of well-ordered dumbbell-shaped ZnO particles, Materials Chemistry and Physics, 2019, 232, 129-136. reported the use of hydrogen peroxide to modify hollow tube alumina to enhance the distribution of active sites on the surface of the material to improve its adsorption capacity, but the washing times were too high and the process was complicated, which was not conducive to industrial application.
[0005] Therefore, there is an urgent need to develop a pseudo-boehmite material that has good pollutant adsorption effect and is suitable for large-scale production and application. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a three-dimensional flower-shaped pseudo-boehmite material with high specific surface area and a preparation method and application thereof.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a three-dimensional flower-shaped pseudo-boehmite material with a high specific surface area, wherein the pseudo-boehmite material is a three-dimensional flower-shaped structure formed by assembling nanosheets.
[0008] The second aspect of the present invention provides a method for preparing the pseudo-boehmite material according to the first aspect, wherein the method comprises the following steps:
[0009] (1) mixing an aluminum salt solution with a molar concentration of 0.02-0.08 mol / L, a surfactant, and an alkaline solution to form a first mixed solution; wherein the aluminum salt solution and the alkaline solution are a mixed solvent composed of alcohol and water;
[0010] (2) dissolving the low-carbon organic ester in a mixed solvent of alcohol and water to form a second mixed solution;
[0011] (3) adding the first mixed solution and the second mixed solution into a rotating liquid film reactor simultaneously for rapid nucleation to form a nucleation slurry;
[0012] (4) subjecting the nucleation slurry obtained in step (3) to microwave hydrothermal crystallization to obtain the three-dimensional flower-shaped high specific surface area pseudo-boehmite material.
[0013] The third aspect of the present invention provides a three-dimensional flower-shaped high specific surface area pseudo-boehmite material prepared by the method described in the second aspect, wherein the pseudo-boehmite material is a three-dimensional flower-shaped structure formed by assembling nanosheets.
[0014] The fourth aspect of the present invention provides the use of the three-dimensional flower-shaped high specific surface area pseudo-boehmite material described in the first aspect or the third aspect in catalysis, adsorption and separation.
[0015] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0016] (1) The pseudo-boehmite material provided by the present invention has a special three-dimensional flower-like structure, which is formed by self-assembly of nanosheets, and can increase the density of adsorption sites, so that it has more adsorption sites, greatly improving the adsorption performance of the pseudo-boehmite material for phosphorus, fluorine and Congo red dye in water.
[0017] (2) The present invention can regulate the (020) crystal plane exposure ratio and specific surface area of pseudo-boehmite. The pseudo-boehmite with a special morphology in the present invention can also give full play to its advantages of large specific surface area and abundant active adsorption hydroxyl group sites on the (020) crystal plane in the process of treating sewage, thereby improving adsorption efficiency and increasing adsorption capacity.
[0018] (3) The preparation method provided by the present invention is simple to operate and has mild reaction conditions. It can synthesize flower-shaped pseudo-boehmite with crystal face selectivity and large specific surface area at a lower cost and higher efficiency, and is easy to realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the XRD spectrum of the pseudo-boehmite prepared in Example 1 of the present invention.
[0020] Figure 2 This is the XRD spectrum of the pseudo-boehmite prepared in Comparative Example 1.
[0021] Figure 3 This is the XRD spectrum of the pseudo-boehmite containing gibbsite impurities prepared in Comparative Example 2.
[0022] Figure 4 This is a SEM image of the pseudo-boehmite prepared in Example 1 of the present invention.
[0023] Figure 5 This is the SEM image of the pseudo-boehmite prepared in Comparative Example 1.
[0024] Figure 6 This is the SEM image of the pseudo-boehmite prepared in Comparative Example 3.
[0025] Figure 7 This is the SEM image of the pseudo-boehmite prepared in Comparative Example 4.
[0026] Figure 8 This is the SEM image of the pseudo-boehmite prepared in Comparative Example 5.
[0027] Fig. 9 This is the SEM image of the pseudo-boehmite prepared in Comparative Example 6.
[0028] Fig.10 The low temperature N of the pseudo-boehmite prepared in Example 1 of the present invention 2 Adsorption-desorption isotherms and pore size distribution diagrams.
[0029] Fig.11 This is a graph showing the adsorption performance of the pseudo-boehmite prepared in Example 1 of the present invention for phosphorus solution.
[0030] Fig.12 This is a curve diagram of the adsorption performance of the pseudo-boehmite prepared in Comparative Example 1 to phosphorus solution.
[0031] Fig.13 This is a graph showing the adsorption performance of the pseudo-boehmite prepared in Example 1 of the present invention to fluorine solution.
[0032] Fig.14 This is a curve diagram of the adsorption performance of the pseudo-boehmite prepared in Comparative Example 1 to fluorine solution.
[0033] Fig.15 This is a graph showing the adsorption performance of the pseudo-boehmite prepared in Example 1 of the present invention to Congo red solution.
[0034] Fig.16 This is a curve diagram of the adsorption performance of the pseudo-boehmite prepared in Comparative Example 1 to Congo red solution. DETAILED DESCRIPTION
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0036] A first aspect of the present invention provides a three-dimensional flower-shaped pseudo-boehmite material with a high specific surface area, wherein the pseudo-boehmite material is a three-dimensional flower-shaped structure formed by assembling nanosheets.
[0037] The pseudo-boehmite material provided by the present invention has a special three-dimensional flower-like structure, which is formed by self-assembly of nanosheets, can increase the density of adsorption sites, so that it has more adsorption sites, which is helpful for adsorbing phosphorus, fluorine and Congo red in water.
[0038] In some embodiments of the present invention, the average particle size of the pseudo-boehmite material is 500-1000nm, for example, 500, 584.1, 599.5, 609.4, 623.9, 817.2, 838.1, 845.2, 872.7, 887.5, 1000nm, and any value within the range of any two of the above values, preferably 584.1-887.5nm, and more preferably 584.1-599.5nm.
[0039] In some embodiments of the present invention, the (020) crystal plane exposure ratio of the pseudo-boehmite material is 10-50%, for example, 10%, 10.66%, 12.06%, 13.44%, 13.66%, 15.87%, 17.29%, 17.33%, 18.87%, 19.25%, 50%, and any value within the range of any two of the above values, preferably 10.66-19.25%, and more preferably 18.87-19.25%.
[0040] In some embodiments of the present invention, the specific surface area of the pseudo-boehmite material is 300-500m 2 / g, for example, 300, 303.52, 324.61, 331.25, 341.77, 384.46, 398.70, 412.37, 430.67, 500m 2 / g, and any value within the range of any two of the above values, preferably 303.52-430.67m 2 / g, more preferably 412.37-430.67m 2 / g.
[0041] The pseudo-boehmite of the present invention has a special morphology and also has a higher (020) crystal plane exposure ratio and specific surface area.
[0042] The second aspect of the present invention provides a method for preparing the three-dimensional flower-shaped high specific surface area pseudo-boehmite material according to the first aspect, wherein the method comprises the following steps:
[0043] (1) mixing an aluminum salt solution with a molar concentration of 0.02-0.08 mol / L, a surfactant, and an alkaline solution to form a first mixed solution; wherein the aluminum salt solution and the alkaline solution are a mixed solvent composed of alcohol and water;
[0044] (2) dissolving the low-carbon organic ester in a mixed solvent of alcohol and water to form a second mixed solution;
[0045] (3) adding the first mixed solution and the second mixed solution into a rotating liquid film reactor simultaneously for rapid nucleation to form a nucleation slurry;
[0046] (4) subjecting the nucleation slurry obtained in step (3) to microwave hydrothermal crystallization to obtain the three-dimensional flower-shaped high specific surface area pseudo-boehmite material.
[0047] The mixed solvent used in step (2) is the same as the mixed solvent used in step (1).
[0048] The invention uses a rotating liquid film reactor to instantaneously nucleate an aluminum salt solution and an alkaline solution in the presence of a surfactant, and adjusts the aluminum salt concentration and solvent composition in the reaction to strengthen the crystal nucleation environment, uses a low-carbon organic ester reaction to slowly release acid and alcohol, uses acid to regulate the reaction pH value and alcohol to construct an inorganic-organic phase interface, and can control the preparation of three-dimensional flower-shaped pseudo-boehmite; microwave heating replaces traditional heating to accelerate the nucleus growth rate and growth uniformity; the surfactant can selectively adsorb on the non-(020) crystal surface of the instantaneous nucleation of the pseudo-boehmite, inhibiting its growth during the crystallization process, and forming a stable nanostructured microsphere with crystal surface selectivity. The nanosheet grows outward and assembles into a nano flower ball during the microwave crystallization process, and stops growing when the reactant is exhausted, resulting in a decrease in surface energy and a reduction in the size of the microsphere, thereby obtaining a three-dimensional flower-shaped pseudo-boehmite adsorption material with a high specific surface area and (020) crystal surface selectivity.
[0049] In some embodiments of the present invention, the molar concentration of the aluminum salt solution is 0.02-0.06 mol / L, for example, 0.02, 0.03, 0.04, 0.05, 0.06 mol / L, and any value within the range of any two of the above values, preferably 0.06 mol / L. If the molar concentration is too low, the purity of the material decreases (gibbsite impurities are generated); if the molar concentration is too high, when it exceeds 0.06 mol / L but is less than 0.1 mol / L, the morphology changes to a rod-like morphology; if it exceeds 0.1 mol / L, the morphology collapses and becomes irregular agglomerates as shown in Comparative Example 1.
[0050] In some embodiments of the present invention, the aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate and their corresponding hydrates.
[0051] In some embodiments of the present invention, the amount of the surfactant used is 0.1-10 mol%, preferably 3 mol%, based on the molar number of aluminum ions in the aluminum salt.
[0052] In some embodiments of the present invention, the surfactant is selected from at least one of cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS) or polyvinylpyrrolidone (PVP), preferably cetyltrimethylammonium bromide (CTAB).
[0053] In some embodiments of the present invention, the molar concentration of the alkaline solution is 0.01-1 mol / L, preferably 0.6-1 mol / L.
[0054] In some embodiments of the present invention, the molar ratio of the aluminum salt to the base is 1:10-50, preferably 1:10-30, and more preferably 1:10-16.7.
[0055] In some embodiments of the present invention, the base is selected from at least one of sodium hydroxide, sodium carbonate, sodium acetate, sodium aluminate, urea, hexamethylenetetramine or ammonia water.
[0056] In some embodiments of the present invention, the alcohol is selected from at least one of methanol, ethanol or ethylene glycol, preferably methanol.
[0057] In some embodiments of the present invention, the mass ratio of alcohol to water in the mixed solvent is 1:1-3, preferably 1:2. Within this mass ratio range, a material with a three-dimensional flower-like structure formed by the assembly of nanosheets can be obtained.
[0058] In some embodiments of the present invention, the amount of the low-carbon organic ester is 10-20%, preferably 10-15%, of the total mass of all mixed solvents and the low-carbon organic ester. Within this amount range, a material having a three-dimensional flower-like structure formed by nanosheet assembly can be obtained. Wherein, "all mixed solvents" refers to the sum of the solvents of the aluminum salt solution and the alkaline solution in step (1) and the solvent of the second mixed solution.
[0059] In some embodiments of the present invention, the low-carbon organic ester is selected from at least one of methyl formate, ethyl acetate, ethyl propionate or propyl propionate, preferably ethyl acetate.
[0060] In some embodiments of the present invention, the rotating liquid film reactor is operated at a rotation speed of 1000-3000 rpm, preferably 1500 rpm.
[0061] In some embodiments of the present invention, the microwave hydrothermal crystallization is performed at a rotation speed of 200-400 rpm, preferably 275 rpm.
[0062] In some embodiments of the present invention, the microwave hydrothermal crystallization temperature is 60-160°C, preferably 80-120°C.
[0063] In some embodiments of the present invention, the microwave hydrothermal crystallization time is 10-60 min, preferably 10-30 min, and more preferably 30 min.
[0064] In some embodiments of the present invention, after the reaction is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral; the product is dried at 60-100°C for 8-24 hours to obtain the target product, three-dimensional flower-shaped high specific surface area pseudo-boehmite.
[0065] According to a particularly preferred embodiment of the present invention, a method for preparing a three-dimensional flower-shaped high specific surface area pseudo-boehmite material, wherein the method comprises the following steps:
[0066] (1) preparing an aluminum salt solution with a molar concentration of 0.02-0.06 mol / L with an aluminum salt, using methanol and water as a mixed solvent (the mass ratio of methanol to water is 1:2), and then adding a surfactant in an amount of 0.1-10% of the amount of the aluminum ion substance to obtain an aluminum salt solution containing a surfactant; the aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate and their corresponding hydrates; the surfactant is selected from at least one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate or polyvinylpyrrolidone;
[0067] According to the concentration of the aluminum salt, an alkaline solution with a molar concentration of 0.01-1 mol / L is prepared with an alkaline compound at a molar ratio of aluminum salt to alkali of 1:10-50, wherein the alkaline compound is selected from at least one of sodium hydroxide, sodium carbonate, sodium acetate, sodium aluminate, urea, hexamethylenetetramine or ammonia water;
[0068] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0069] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.1-0.5 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at a rate of 50 mL / min for rapid nucleation by a peristaltic pump, and collecting the nucleated slurry at the slurry outlet;
[0070] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 200-400 rpm, add the nucleation slurry into the reactor, crystallize at 60-160° C. for 10-60 min, cool to room temperature after crystallization, centrifuge the product, and wash with water until neutral; dry the product at 60-100° C. for 8-24 hours to obtain the target product, a three-dimensional flower-shaped high specific surface area pseudo-boehmite.
[0071] The third aspect of the present invention provides a pseudo-boehmite material prepared by the method described in the second aspect, wherein the pseudo-boehmite material is a three-dimensional flower-like structure formed by assembling nanosheets.
[0072] In some embodiments of the present invention, the average particle size of the pseudo-boehmite material is 500-1000 nm, preferably 584.1-887.5 nm, and more preferably 584.1-599.5 nm.
[0073] In some embodiments of the present invention, the (020) crystal plane exposure ratio of the pseudo-boehmite material is 10-50%, preferably 10.66-19.25%, and more preferably 18.87-19.25%.
[0074] In some embodiments of the present invention, the specific surface area of the pseudo-boehmite material is 300-500m 2 / g, preferably 303.52-430.67m 2 / g, more preferably 412.37-430.67m 2 / g.
[0075] The fourth aspect of the present invention provides the use of the three-dimensional flower-shaped high specific surface area pseudo-boehmite material described in the first aspect or the third aspect in catalysis, adsorption and separation.
[0076] In some embodiments of the present invention, the application is the adsorption of phosphorus, fluorine and Congo red in water.
[0077] The pseudo-boehmite material prepared by the invention has the advantages of crystal face selectivity, large specific surface area and the like, and when used as an adsorption material, the adsorption performance is greatly improved.
[0078] The present invention will be described in detail below through examples.
[0079] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained through commercial channels.
[0080] Example 1
[0081] This example is used to illustrate the preparation of pseudo-boehmite material.
[0082] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0083] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0084] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0085] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0086] Example 2
[0087] This example is used to illustrate the preparation of pseudo-boehmite material.
[0088] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.02 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0089] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0090] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0091] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0092] Example 3
[0093] This example is used to illustrate the preparation of pseudo-boehmite material.
[0094] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 0.6 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0095] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2), and stirring to obtain a mixed slurry;
[0096] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0097] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0098] Example 4
[0099] This example is used to illustrate the preparation of pseudo-boehmite material.
[0100] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium aluminate is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0101] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0102] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0103] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0104] Example 5
[0105] This example is used to illustrate the preparation of pseudo-boehmite material.
[0106] (1) Aluminum nitrate is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0107] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0108] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0109] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0110] Example 6
[0111] This example is used to illustrate the preparation of pseudo-boehmite material.
[0112] (1) Aluminum sulfate is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium acetate is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0113] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0114] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0115] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0116] Example 7
[0117] This example is used to illustrate the preparation of pseudo-boehmite material.
[0118] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant CTAB is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0119] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0120] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0121] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 120° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0122] Example 8
[0123] This example is used to illustrate the preparation of pseudo-boehmite material.
[0124] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant SDS is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0125] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0126] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0127] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0128] Example 9
[0129] This example is used to illustrate the preparation of pseudo-boehmite material.
[0130] (1) Aluminum chloride is used to prepare 40 mL of a salt solution with a molar concentration of 0.06 mol / L, and sodium hydroxide is used to prepare 40 mL of an alkaline solution with a concentration of 1 mol / L, wherein methanol and water are used as a mixed solvent (the mass ratio of methanol to water is 1:2), and a surfactant PVP is added to the above salt solution, and its amount is 3% of the amount of aluminum ion substance in the salt solution;
[0131] (2) dissolving ethyl acetate (the amount used is 10% of the total mass of all mixed solvents and ethyl acetate) in a mixed solvent of alcohol and water (the mass ratio of methanol to water is 1:2);
[0132] (3) starting the rotating liquid film reactor, setting the stator-rotor gap of the reactor to 0.4 mm and the rotation speed to 1500 rpm, delivering the mixed solution in step (1) and step (2) to the reactor at the same rate by a peristaltic pump for rapid nucleation, and collecting the nucleated slurry at the slurry outlet;
[0133] (4) Turn on the microwave reactor and set the speed of the microwave reactor to 275 rpm. Add the nucleation slurry obtained in step (3) into the reactor and crystallize at 80° C. for 30 min. After the crystallization is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral. The product is dried at 60° C. for 8 h to obtain the target product, pseudo-boehmite.
[0134] Example 10
[0135] Pseudo-boehmite was prepared according to the method of Example 1, except that the mass ratio of methanol to water was 1:1, and the mass ratio of methanol, water and ethyl acetate was 9:9:2.
[0136] Embodiment 11
[0137] Pseudo-boehmite was prepared according to the method of Example 1, except that the ethyl acetate in step (2) was replaced by methyl formate.
[0138] Example 12
[0139] Pseudo-boehmite was prepared according to the method of Example 1, except that the amount of ethyl acetate used was 15% of the total mass of the mixed solvent and ethyl acetate.
[0140] Comparative Example 1
[0141] Pseudo-boehmite was prepared according to the method of Example 1, except that the molar concentration of the aluminum chloride salt solution was 0.2 mol / L.
[0142] Comparative Example 2
[0143] Pseudo-boehmite was prepared according to the method of Example 1, except that the molar concentration of the aluminum chloride salt solution was 0.01 mol / L.
[0144] Comparative Example 3
[0145] Pseudo-boehmite was prepared according to the method of Example 1, except that deionized water was used as solvent for the aluminum chloride salt solution and the alkaline solution.
[0146] Comparative Example 4
[0147] Pseudo-boehmite was prepared according to the method of Example 1, except that in step (1), the surfactant CTAB was not added to the aluminum chloride salt solution.
[0148] Comparative Example 5
[0149] (1) Aluminum sulfate was used to prepare 100 mL of a salt solution with a molar concentration of 0.1 mol / L, and sodium aluminate was used to prepare 100 mL of a salt solution with a molar concentration of 0.45 mol / L, without adding a surfactant;
[0150] (2) Under stirring, the two solutions are added to a three-necked flask at the same rate using a constant pressure dropping funnel for reaction. After the addition is completed, the temperature is raised to 80°C for reaction for 2 hours. After the reaction is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral; the product is placed at 60°C and dried for 8 hours to obtain the target product, pseudo-boehmite.
[0151] Comparative Example 6
[0152] Pseudo-boehmite was prepared according to the method of Example 1, except that ethyl acetate was not added in step (2).
[0153] Comparative Example 7
[0154] Pseudo-boehmite was prepared according to the method of Example 1, except that a rotating liquid film reactor was not used in step (3), and magnetic stirring and mixing were performed at a rotation speed of 1500 rpm.
[0155] Test Example 1
[0156] The crystal structure of the samples was characterized by XRD-6000 X-ray powder diffractometer produced by Shimadzu Corporation of Japan.
[0157] according to Figure 1 The characteristic crystal plane diffraction peaks of the pseudo-boehmite prepared in Example 1 appear at 2θ=13.6° / 020, 28.1° / 120, 38.3° / 031, 49.2° / 200, 64.8° / 002 and 71.7° / 171, respectively, corresponding to the standard card PDF#21-1307. Figure 1 There are no impurity peaks in the sample, indicating that the sample has a single crystal phase and a complete crystal structure.
[0158] according to Figure 2 The characteristic crystal plane diffraction peaks of the pseudo-boehmite prepared in Comparative Example 1 appear at 2θ=14.6° / 020, 28.1° / 120, 38.3° / 031, 49.1° / 200, 65.1° / 002 and 72.1° / 171, respectively, corresponding to the standard card PDF#21-1307.
[0159] according to Figure 3 The characteristic crystal plane diffraction peaks of the pseudo-boehmite prepared in Comparative Example 2 appear at 2θ=13.6° / 020, 28.1° / 120, 38.3° / 031, 49.2° / 200, 64.8° / 002 and 71.7° / 171, respectively, which are consistent with the peak type and peak position of pseudo-boehmite on the JCPDS standard card (PDF#21-1307), indicating that the synthetic product contains pseudo-boehmite. However, a typical impurity peak of gibbsite appears at about 2θ=13.6°. This indicates that the prepared pseudo-boehmite contains gibbsite impurities.
[0160] Test Example 2
[0161] The morphology of the prepared samples was observed using a German ZEISS Supra 55 scanning electron microscope (SEM).
[0162] The pseudo-boehmite prepared in Examples 1-12 exhibits a three-dimensional flower-like structure formed by the assembly of nanosheets. Figure 4 It presents a flower-like morphology, and the flower-like structures are uniform in size.
[0163] The pseudo-boehmite prepared in Comparative Example 1 has irregular block agglomeration, and the grain size cannot be counted. Figure 5 shown.
[0164] The pseudo-boehmite prepared in Comparative Example 3 showed flake agglomeration, such as Figure 6 shown.
[0165] The pseudo-boehmite prepared in Comparative Example 4 is aggregated in agglomerates, such as Figure 7shown.
[0166] The pseudo-boehmite prepared in Comparative Example 5 is needle-shaped aggregates, such as Figure 8 shown.
[0167] The pseudo-boehmite prepared in Comparative Example 6 is a flake aggregate, such as Fig. 9 shown.
[0168] Test Example 3
[0169] (020) crystal plane exposure ratio:
[0170] Since the (020), (200) and (002) crystal planes are directly related to the dimensions along the b, c and a axes, these three crystal planes are selected to participate in the calculation of the crystal plane exposure ratio. The areas (S) of the three crystal planes are calculated by the Scherrer formula, and the exposure ratio of the (020) crystal plane = S (020) / (S (020) +S (200) +S (002) ).
[0171] Average particle size:
[0172] The morphology was characterized using a 20kV Zeiss Supra 55 scanning electron microscope (SEM). An appropriate amount of the powder sample to be tested was added to anhydrous ethanol, and the powder was evenly dispersed in the ethanol under ultrasonic action. The evenly dispersed liquid was dropped on a single crystal silicon wafer. After the ethanol evaporated, the silicon wafer with the sample was gold-sprayed to increase the conductivity of the sample, and then SEM was performed on it. The characterization results were imported into Nano Measurer to calculate the average particle size.
[0173] Specific surface area:
[0174] The specific surface area of the samples was measured using the BET method using an American Micromeritics ASAP 2390 specific surface meter. Fig.10 Medium and low temperature N 2 The adsorption-desorption isotherms are typical type IV isotherms, indicating that the samples contain a large number of mesopores; the hysteresis loop is between H3 and H4, indicating that the samples are formed by the aggregation and stacking of loose flaky particles and have a slit pore structure.
[0175] Maximum adsorption capacity of phosphorus:
[0176] The adsorption performance of pseudo-boehmite was tested using the test method in the literature (Tuan Van Truong, Dong-Jin Kim. Synthesis of high quality boehmite and γ-alumina for phosphorus removal from water works sludge by extraction and hydrothermal treatment, Environmental Research., 2022, 212, 113448.): 0.02 g of pseudo-boehmite was mixed with 50 mL of a 50 ppm phosphorus solution (using potassium dihydrogen phosphate as a raw material to prepare a phosphate solution) in a conical flask, and then placed in a shaker, and shaken at 150 rpm in a 25 ° C water bath. The concentration at different times was detected by ion chromatography. The results of Example 1 and Comparative Example 1 are shown in Fig.11 , Fig.12 .
[0177] Maximum adsorption capacity of fluorine:
[0178] The adsorption performance of pseudo-boehmite was tested by the test method in the literature (Dongjuan Kang, Xiaolin Yu, et al. Performance and mechanism of Mg / Fe layered double hydroxides for fluoride and arsenate removal from aqueous solution, Chemical Engineering Journal., 2013, 228, 731-740.): 0.0375 g of pseudo-boehmite was mixed with 50 mL of 50 ppm fluoride solution (sodium fluoride was used as raw material to prepare fluoride ion solution) in a conical flask, and then placed in a shaker, and shaken at a speed of 150 rpm in a water bath at 25°C. The concentration at different times was detected by ion chromatography. The results of Example 1 and Comparative Example 1 are shown in FIG. Fig.13 , Fig.14 .
[0179] Maximum adsorption capacity of Congo red:
[0180] The adsorption performance of pseudo-boehmite was tested by the test method in the literature (Guangci Li, Yuanyuan Sun and Xuebing Li, et al. Adsorption of Congo red from water with spindle-like boehmite: the role of lattice plane (020), RSC Adv, 2016, 6: 11855-11862.): 0.01 g of pseudo-boehmite was mixed with 50 mL of a 300 ppm Congo red solution (Congo red was used as a raw material to prepare a Congo red solution) in a conical flask, and then placed in a shaker, and shaken at a speed of 150 rpm in a 25°C water bath. The concentration at different times was detected by a UV spectrophotometer. The results of Example 1 and Comparative Example 1 are shown in Fig.15 , Fig.16 .
[0181] The above test results are shown in Table 1.
[0182] Table 1
[0183]
[0184] From the results in Table 1, it can be seen that the maximum adsorption of phosphorus, fluorine and Congo red by the pseudo-boehmite prepared by the present invention far exceeds that of the comparative example, and has a higher (020) crystal plane exposure ratio and specific surface area. From the comparison between Example 4 and Comparative Example 5, it can be seen that although the (020) crystal plane exposure ratio and specific surface area are similar, due to the difference in morphology, the pseudo-boehmite material with a three-dimensional flower-like structure formed by nanosheet assembly prepared in Example 4 shows significantly improved adsorption performance.
[0185] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A three-dimensional flower-shaped high specific surface area pseudo-boehmite material, characterized in that: The pseudo-boehmite material is a three-dimensional flower-like structure formed by assembling nanosheets.
2. The pseudo-boehmite material according to claim 1, wherein: The average particle size of the pseudo-boehmite material is 500-1000 nm, preferably 584.1-887.5 nm, and more preferably 584.1-599.5 nm; Preferably, the (020) crystal plane exposure ratio of the pseudo-boehmite material is 10-50%, preferably 10.66-19.25%, and further preferably 18.87-19.25%; Preferably, the specific surface area of the pseudo-boehmite material is 300-500m 2 / g, preferably 303.52-430.67m 2 / g, more preferably 412.37-430.67m 2 / g.
3. A method for preparing the pseudo-boehmite material according to claim 1 or 2, characterized in that: The method comprises the following steps: (1) mixing an aluminum salt solution with a molar concentration of 0.02-0.08 mol / L, a surfactant, and an alkaline solution to form a first mixed solution; wherein the aluminum salt solution and the alkaline solution are a mixed solvent composed of alcohol and water; (2) dissolving the low-carbon organic ester in a mixed solvent consisting of alcohol and water to form a second mixed solution; (3) adding the first mixed solution and the second mixed solution into a rotating liquid film reactor simultaneously for rapid nucleation to form a nucleation slurry; (4) subjecting the nucleation slurry obtained in step (3) to microwave hydrothermal crystallization to obtain the three-dimensional flower-shaped high specific surface area pseudo-boehmite material.
4. The method according to claim 3, wherein: The molar concentration of the aluminum salt solution is 0.02-0.06 mol / L, preferably 0.06 mol / L; Preferably, the aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate and their corresponding hydrates.
5. The method according to claim 3 or 4, wherein: The amount of the surfactant is 0.1-10 mol% of the molar number of aluminum ions in the aluminum salt, preferably 3 mol%; Preferably, the surfactant is selected from at least one of cetyltrimethylammonium bromide, sodium lauryl sulfate or polyvinylpyrrolidone, preferably cetyltrimethylammonium bromide.
6. The method according to any one of claims 3 to 5, wherein: The molar concentration of the alkaline solution is 0.01-1 mol / L, preferably 0.6-1 mol / L; Preferably, the molar ratio of the aluminum salt to the base is 1:10-50, preferably 1:10-30, and more preferably 1:16.7; Preferably, the base is selected from at least one of sodium hydroxide, sodium carbonate, sodium acetate, sodium aluminate, urea, hexamethylenetetramine or ammonia water; Preferably, the alcohol is selected from at least one of methanol, ethanol or ethylene glycol, preferably methanol; Preferably, the mass ratio of alcohol to water in the mixed solvent is 1:1-3, preferably 1:
2.
7. The method according to any one of claims 3 to 6, wherein: The amount of the low-carbon organic ester is 10-20% of the total mass of all mixed solvents and the low-carbon organic ester, preferably 10-15%; Preferably, the low-carbon organic ester is selected from at least one of methyl formate, ethyl acetate, ethyl propionate or propyl propionate, preferably ethyl acetate; Preferably, the rotating liquid film reactor is operated at a rotation speed of 1000-3000 rpm, preferably 1500 rpm.
8. The method according to any one of claims 3 to 7, wherein: The microwave hydrothermal crystallization is carried out at a rotation speed of 200-400 rpm, preferably 275 rpm; Preferably, the temperature of the microwave hydrothermal crystallization is 60-160°C, preferably 80-120°C; Preferably, the microwave hydrothermal crystallization time is 10-60 min, preferably 10-30 min, and more preferably 30 min; Preferably, after the reaction is completed and cooled to room temperature, the product is centrifuged and washed with water until neutral; the product is dried at 60-100° C. for 8-24 hours to obtain a three-dimensional flower-shaped pseudo-boehmite material with a high specific surface area.
9. A three-dimensional flower-shaped high specific surface area pseudo-boehmite material prepared by the method according to any one of claims 3 to 8, characterized in that: The pseudo-boehmite material is a three-dimensional flower-like structure formed by the assembly of nanosheets; Preferably, the average particle size of the pseudo-boehmite material is 500-1000 nm, preferably 584.1-887.5 nm, and more preferably 584.1-599.5 nm; Preferably, the (020) crystal plane exposure ratio of the pseudo-boehmite material is 10-50%, preferably 10.66-19.25%, and further preferably 18.87-19.25%; Preferably, the specific surface area of the pseudo-boehmite material is 300-500m 2 / g, preferably 303.52-430.67m 2 / g, more preferably 412.37-430.67m 2 / g.
10. Use of the three-dimensional flower-shaped high specific surface area pseudo-boehmite material according to any one of claims 1 to 2 and 9 in catalysis, adsorption and separation; Preferably, the application is the adsorption of phosphorus, fluorine and Congo red in water.
Citation Information
Patent Citations
Hydrothermal method for preparing series of special-shaped graded pseudo-boehmite
CN101704538A
Crystal face selective growth boehmite and preparation method thereof
CN111924865A
Spherical aluminum oxide with flower-cluster-shaped lamellar structure on surface and preparation method of spherical aluminum oxide
CN114180607A
Flaky AlOOH material as well as preparation method and application thereof
CN117000220A